Sludge carbon loaded schwertmannite immobilized iron-sulfur reducing bacteria composite material as well as preparation method and application thereof

Through the preparation of the solid-loaded iron-sulfur reducing bacteria composite of Sert-loaded Serb, the problem of difficult to stably remove heavy metal pollution in acidic mine wastewater in the prior art is solved, and efficient and stable heavy metal removal effect is achieved.

CN119528348AActive Publication Date: 2025-02-28CENT SOUTH UNIV +1

Patent Information

Application Number
CN202510091520.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-28
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to achieve stable removal when dealing with heavy metal pollution in acid mine wastewater, and the adsorption capacity is limited, making it prone to secondary pollution.

Method used

A composite material of solid-loaded iron-sulfur reduction bacteria with sewage peat loaded by Schneida mineral was developed, and sludge was prepared by high-temperature pyrolysis, and reacted with ferrous sulfate and hydrogen peroxide to form Schneida mineral. Then, iron-sulfur reduction bacteria were cultured in the culture medium, and the composite material was obtained by solid-liquid separation.

Benefits of technology

The composite material has excellent adsorption performance and stability, and can efficiently fix heavy metal ions. It is especially suitable for the treatment of acidic mine wastewater, with high removal efficiency, adaptable to acidic environments, and can be recycled and recycled.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528348A_ABST
    Figure CN119528348A_ABST
Patent Text Reader

Abstract

The invention discloses a sludge carbon loaded Schwertmannite immobilized iron-sulfur reducing bacteria composite material as well as a preparation method and application thereof. The method comprises the following steps: performing high-temperature pyrolysis on sludge to obtain sludge carbon; mixing the sludge carbon with a ferrous sulfate solution, then adding a hydrogen peroxide solution to carry out oxidation reaction, and carrying out solid-liquid separation to obtain a sludge carbon loaded Schwertmannite material; and adding the sludge carbon-loaded Schwertmannite material into a culture medium containing iron-sulfur reducing bacteria, carrying out bacterial culture until the culture medium is black, and carrying out solid-liquid separation to obtain the sludge carbon-loaded Schwertmannite material. The obtained mineral microorganism composite material is excellent in adsorption performance, large in adsorption capacity and high in stability, can efficiently remove heavy metal ions such as Sb (V), Cd (II) and Pb (II), and is particularly suitable for repairing heavy metal pollution in mining areas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to mineral microbial materials, in particular to a sludge charcoal-loaded Schweiner mineral-immobilized iron-sulfur-reducing bacteria composite material, and also to a preparation method and application thereof, belonging to the technical field of environmental protection. Background Art

[0002] A large amount of acid mine drainage (AMD) is produced during metal mining, which is the main source of heavy metal pollution. Sulfate minerals are the main associated minerals in the AMD environment, including Schroeder mineral (Sch), jarosite and hydroxysulfate green rust, and their formation process is often accompanied by the fixation of heavy metals. Since these associated minerals are in a metastable state in the environment, they are prone to further crystal phase transformation under redox conditions to form structurally stable goethite and hematite, etc. In this process, some of the fixed heavy metals will be released into the environment, posing a serious threat to the surrounding water ecology and agricultural product safety.

[0003] Sch and sulfate-reducing bacteria (SRB) are important active components in AMD sediments in mining areas and have a significant impact on the heavy metal environment. The Sch structure has strong flexibility in regulating the size and charge of metal ions. Heavy metals can replace different structural sites and accumulate inside the minerals at the same time, making Sch an important host mineral for heavy metals in the mining environment. SRB can utilize free SO4 2- As an electron acceptor, Sch can reduce hexavalent S, promote the biomineralization of heavy metals, and use extracellular polymers (EPS) to fix heavy metals through enzymatic action. However, Sch is a metastable mineral initially formed by the hydrolysis of Fe(III) in the AMD environment, and it is easy to undergo secondary phase transformation. During the phase transformation process, heavy metals will be released back into the environment, causing environmental pollution. In addition, direct exposure of microorganisms to acidic environments and heavy metal-contaminated environments will also inhibit the activity of microorganisms and reduce their ability to fix heavy metals.

[0004] In the prior art, sulfate minerals or sulfate-reducing bacteria are directly used to adsorb and remove heavy metals, which makes it impossible to stably remove heavy metals, limits the adsorption capacity, and easily generates secondary pollution.

[0005] Therefore, it is of great significance to develop a new type of mineral-microbial composite material to achieve efficient and stable remediation of AMD pollution in mining areas, thereby reducing the pollution of the mining environment. Summary of the invention

[0006] In view of the shortcomings of the prior art, the first object of the present invention is to provide a composite material of sewage sludge charcoal loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria. The material has a large specific surface area, high activity, excellent adsorption performance, strong stability, and can adapt to acidic environments.

[0007] The second object of the present invention is to provide a method for preparing a composite material of sewage sludge-loaded Schweiner mineral-immobilized iron-sulfur-reducing bacteria. The method is simple, low-cost and suitable for industrial production.

[0008] The third object of the present invention is to provide an application of a composite material of sewage sludge charcoal loaded with Schweiner mineral and immobilized iron-sulfur-reducing bacteria. The material can effectively adsorb heavy metal ions, has a large adsorption capacity and high removal efficiency.

[0009] In order to achieve the above technical objectives, the present invention provides a method for preparing a composite material of sludge charcoal loaded with Scherrer mineral and immobilized iron-sulfur-reducing bacteria, the method comprising: subjecting sludge to high-temperature pyrolysis to obtain sludge charcoal; mixing the sludge charcoal with a ferrous sulfate solution and then adding a hydrogen peroxide solution to carry out an oxidation reaction, and performing solid-liquid separation to obtain a sludge charcoal loaded with Scherrer mineral material; adding the sludge charcoal loaded with Scherrer mineral material to a culture medium containing iron-sulfur-reducing bacteria and carrying out bacterial culture until the culture medium turns black, and then performing solid-liquid separation to obtain the composite material.

[0010] The present invention can greatly improve the adsorption performance and stability of the material by loading the iron-sulfur reducing bacteria on the matrix material of the sludge charcoal. Firstly, the sludge charcoal has a strong fixation ability for heavy metals in the water body, which can significantly reduce the bioavailability and toxicity of heavy metals in the water body. Secondly, the sludge charcoal can effectively inhibit the phase transformation process of the sludge charcoal and enhance the fixation ability of the sludge charcoal for (class) heavy metals. Thirdly, the porous structure, high specific surface area and rich functional group structure of the sludge charcoal can provide a better living environment for microorganisms, enhance the activity of microorganisms, and further enhance the fixation ability of microorganisms for heavy metals. Through the synergistic effect of the three, the adsorption performance and stability of the material are significantly improved.

[0011] In addition, the present invention synthesizes Schrödinger mineral in a system containing sludge carbon, which can enhance the stability of the sludge carbon loaded with Schrödinger mineral. Part of the Schrödinger mineral can be attached to the surface of the sludge carbon by strong interaction, and has better stability than the traditional complex formed by ball milling of sludge carbon and Schrödinger mineral.

[0012] As a preferred solution, the sludge is municipal sludge or printing and dyeing sludge.

[0013] As a preferred solution, the water content of the sludge does not exceed 10wt%.

[0014] As a preferred solution, the sludge is dried at 40-50° C. until the moisture content does not exceed 10 wt %.

[0015] As a preferred solution, the conditions for high-temperature pyrolysis are: the atmosphere is a protective atmosphere, the temperature is 400-600° C., and the time is 2-3 hours.

[0016] As a preferred solution, the protective atmosphere is nitrogen gas, and the flow rate of the nitrogen gas is 30-50 mL / min.

[0017] As a preferred solution, the particle size of the sludge carbon is 200 mesh.

[0018] As a preferred solution, the mass ratio of the sludge charcoal to the iron element in ferrous sulfate is 0.5~2:1.

[0019] As a preferred solution, the molar concentration of the ferrous sulfate is 0.06-0.1 mol / L.

[0020] As a preferred embodiment, the mass concentration of hydrogen peroxide in the hydrogen peroxide solution in the reaction system is 11.12-16.67 g / L.

[0021] As a preferred solution, the mass concentration of the hydrogen peroxide solution is 30-50%.

[0022] As a preferred solution, the particle size of the sludge carbon-loaded Schmidt mineral material is 200 meshes.

[0023] As a preferred solution, the solid obtained after solid-liquid separation is washed with acid and water until the pH value of the washing liquid remains stable, and then the solid is freeze-dried and ground and sieved.

[0024] As a preferred solution, the washing times are 3 to 5 times.

[0025] As a preferred solution, the acid solution is dilute nitric acid, and the pH value of the dilute nitric acid is 1.5-2.5.

[0026] As a preferred embodiment, the iron-sulfur reducing bacteria is Cedecea sp. ISRB13.

[0027] As a preferred solution, the freeze-drying temperature is -60 to -80°C.

[0028] As a preferred solution, the iron-sulfur reducing bacteria is pre-activated in LB medium for 12 to 24 hours.

[0029] As a preferred solution, the sewage sludge charcoal loaded with Schreiber mineral material is added to the culture medium containing iron-sulfur reducing bacteria, and then sterile liquid paraffin is added to seal the liquid surface. The thickness of the sterile liquid paraffin is 2-3 cm.

[0030] As a preferred solution, the bacterial culture conditions are: temperature of 25-35°C and time of 24-48h.

[0031] As a preferred solution, the concentration of the bacterial strain after bacterial culture is 5~10×10 9 CFU / mL.

[0032] As a preferred solution, the solid product obtained by solid-liquid separation after the bacterial culture is completed is washed with physiological saline and then freeze-dried to obtain a composite material of sewage sludge loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria.

[0033] As a preferred solution, the washing times are 3 to 5 times. The freeze drying temperature is -60 to -80°C.

[0034] As a preferred solution, the freeze-dried solid is ground and sieved.

[0035] As a preferred solution, the particle size of the sludge carbon-loaded Schweiner mineral-immobilized iron-sulfur-reducing bacteria composite material is 200 meshes.

[0036] The present invention also provides a sludge carbon-loaded Schweiner mineral-immobilized iron-sulfur-reducing bacteria composite material, which is prepared by the above method.

[0037] The present invention also provides an application of a composite material of sewage sludge loaded with Schweiner mineral and immobilized iron-sulfur-reducing bacteria, which is used for adsorbing and removing heavy metal ions in liquid.

[0038] As a preferred solution, it is used for adsorption and removal of heavy metal ions in wastewater.

[0039] As a preferred solution, the wastewater is acidic mine wastewater, and the pH value of the wastewater is 4-6.

[0040] As a preferred solution, the heavy metal ions include at least one of Sb(V), Cd(II), and Pb(II).

[0041] As a preferred solution, the dosage of the sludge carbon-loaded Schweiner mineral-immobilized iron-sulfur-reducing bacteria composite material in wastewater is 1-2 g / L.

[0042] As a preferred solution, the concentration of heavy metal ions in the wastewater is 50-200 ppm.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) The sludge charcoal-loaded Schweiner mineral-immobilized iron-sulfur-reducing bacteria composite material of the present invention has the advantages of large specific surface area, high activity, excellent adsorption performance, strong stability, ability to adapt to acidic environment, and recyclability;

[0045] (2) The composite material can efficiently fix heavy metal ions such as Sb(V), Cd(II), and Pb(II). It has a small dosage and a large adsorption capacity. It can effectively remove heavy metals from water bodies. It is particularly suitable for the treatment of toxic heavy metal ions in acidic mine wastewater and has broad application prospects.

[0046] (3) The present invention uses microorganisms and Schiff minerals widely existing in nature, as well as sludge solid waste as raw materials, which have a wide source of raw materials and low cost;

[0047] (4) The preparation method is simple, requires little investment, does not require special equipment, and the process is easy to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The XRD patterns of Schrödinger mineral (Sch), sewage sludge (SC) and the composite material of sewage sludge loaded with Schrödinger mineral-immobilized iron-sulfur-reducing bacteria (SC / Sch-Fe / SRB) prepared in Example 1 of the present invention.

[0049] Figure 2 Scanning electron micrographs of Schroeder mineral (A) and sewage sludge (B).

[0050] Figure 3 This is a scanning electron microscope image of the sludge charcoal-loaded Schweiner mineral-immobilized iron-sulfur-reducing bacteria composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0051] The present invention is further described in detail below with reference to examples and drawings, but the implementation manner and protection scope of the present invention are not limited thereto.

[0052] Example 1

[0053] A preparation method of a sludge charcoal-loaded Schroeder mineral-immobilized iron-sulfur-reducing bacteria composite material (SC / Sch-Fe / SRB), the specific steps are as follows:

[0054] The selected strain is Cedecea sp. ISRB13, a microorganism with iron-sulfur reduction function obtained by the applicant from mineral soil in the early stage. The strain was deposited in Guangdong Microbiological Collection Center on December 19, 2023, with the deposit number GDMCC NO.64081.

[0055] Preparation of sewage sludge charcoal (SC): Municipal sludge was placed in an oven at 50°C and dried to a moisture content of 8%. The dried sludge was placed in a tubular furnace for anaerobic pyrolysis at 600°C for 2 h. The nitrogen flow rate was controlled at 50 mL / min during the pyrolysis. The pyrolysis sample was ground and passed through a 200-mesh sieve to obtain sewage sludge charcoal.

[0056] Preparation of sludge-loaded Schrödinger mineral material (SC / Sch): 27.80 g of ferrous sulfate heptahydrate (FeSO4·7H2O) was dissolved in 1 L of deionized water (0.1 mol / L), 11.2 g of the above sludge was added, and after stirring evenly, 15 mL of 30% hydrogen peroxide (H2O2) solution was slowly added using a peristaltic pump. After fully reacting at room temperature for 48 h, the mixture was centrifuged at 8000 rpm for 5 min, and the solid in the mixture was collected and washed with dilute nitric acid solution with a pH of 2 and deionized water until the pH value of the washing solution remained constant. Then, the washed solid was freeze-dried at -68 ° C for 48 h, and then ground through a 200 mesh sieve to obtain a sludge-loaded Schrödinger mineral sample.

[0057] Preparation of SC / Sch-Fe / SRB material: After the above-screened microorganism Cedecea sp. ISRB13 (1 mL of strain stock solution) was activated in LB medium (100 mL) for 24 h, the above-mentioned sludge-loaded Schrödinger mineral material was added, mixed and shaken, and sterile liquid paraffin was gently added to seal the liquid surface. The thickness of the sterile liquid paraffin was 3 cm. The stopper was tightly plugged and cultured at a constant temperature of 30 ° C for 24 h until the entire culture medium showed a thick black color (the bacterial concentration at this time was 5×10 9 CFU / mL), and obtain a modified product solution. After centrifugation at 8000 rpm for 3 minutes, the solution was washed with physiological saline, and the operation was repeated 3 times. The washed solid was freeze-dried at -80°C for 24 hours and then ground through a 200-mesh sieve to obtain the SC / Sch-Fe / SRB material.

[0058] Comparative Example 1

[0059] Preparation of sludge charcoal loaded microorganisms (SC-Fe / SRB): After activating the microorganism Cedecea sp. ISRB13 screened in Example 1 in LB medium for 24 h, add the sludge charcoal material prepared in Example 1, the mass ratio of microorganism to sludge charcoal material is 1:50, mix and shake well, gently add sterile liquid paraffin to seal the liquid surface, the thickness of sterile liquid paraffin is 3 cm, plug the stopper, and culture at a constant temperature of 30°C for 24 h until the entire culture medium presents a thick black color to obtain a modified product solution. After centrifugation at 8000 rpm for 3 minutes, wash with physiological saline, repeat the operation 3 times, freeze-dry the washed solid at -60°C for 24 h, and grind through a 200-mesh sieve to obtain the SC-Fe / SRB material.

[0060] Comparative Example 2

[0061] Preparation of Schmite (Sch): 22.24 g of FeSO4·7H2O was dissolved in 1 L of deionized water (DIW) and stirred thoroughly. During stirring, 15 mL of hydrogen peroxide (H2O2, 30%) was slowly added using a peristaltic pump. After the mixture was allowed to react for 24 h, the solids in the mixture were collected by centrifugation. Subsequently, the solids were washed with a dilute acid solution (pH ≈ 2) and deionized water until the pH value of the washing solution remained stable. Finally, the obtained solids were freeze-dried and stored in a desiccator. To ensure the consistency of the mineral particles, the minerals were ground and sieved through a 200-mesh sieve before use.

[0062] Preparation of Sch-Fe / SRB: After the microorganism Cedecea sp. ISRB13 screened in Example 1 was activated in LB medium for 24 h, the above-mentioned Sch-Fe / SRB material was added, mixed and shaken, and sterile liquid paraffin was gently added to seal the liquid surface. The thickness of the sterile liquid paraffin was 3 cm. The stopper was tightly plugged and cultured at a constant temperature of 30°C for 24 h until the entire culture medium showed a thick black color to obtain a modified product solution. After centrifugation at 8000 rpm for 3 minutes, it was washed with physiological saline, and the operation was repeated 3 times. The washed solid was freeze-dried at -60°C for 24 h and then ground through a 200-mesh sieve to obtain the Sch-Fe / SRB material.

[0063] Comparative Example 3

[0064] The sludge charcoal in Example 1 and the Schrödinger mineral in Comparative Example 2 were mixed and ball-milled in a ratio of 2:1 of the mass ratio of the Fe element in the sludge charcoal to the Schrödinger mineral to obtain a composite material of ordinary sludge charcoal and Schrödinger mineral (N-SC / Sch).

[0065] After the above-screened microorganism Cedecea sp. ISRB13 was activated in LB medium for 24 h, the above-mentioned ordinary sludge and Schrödinger mineral composite material (N-SC / Sch) was added, mixed and shaken, and sterile liquid paraffin was gently added to seal the liquid surface. The thickness of the sterile liquid paraffin was 3 cm. The stopper was plugged tightly and cultured at a constant temperature of 30°C for 24 h until the entire culture medium showed a thick black color to obtain a modified product solution. After centrifugation at 8000 rpm for 3 minutes, it was washed with physiological saline, and the operation was repeated 3 times. The washed solid was freeze-dried at -80°C for 24 h and then ground through a 200-mesh sieve to obtain the N-SC / Sch-Fe / SRB material.

[0066] X-ray diffraction analysis (XRD) of SC, Sch and SC / Sch-Fe / SRB materials is shown in Figure 2. Figure 1 As shown in the figure, the SC / Sch-Fe / SRB material significantly changed the characteristic diffraction peaks of Schrödinger mineral and SC, especially near the diffraction peak of 35 degrees (characteristic diffraction peak of Sch). The diffraction peak intensity of the SC / Sch-Fe / SRB material was significantly enhanced compared with that of the SC material, indicating that the Schrödinger mineral was successfully loaded on the sludge, and the prepared material is a new mineral material. The scanning electron microscope (SEM) images were analyzed, and the results are shown in the figure. Figure 2 and Figure 3 As shown, the morphology of the Schmidtite is a spherical structure ( Figure 2 (A)), sludge charcoal has a lamellar structure ( Figure 2 (B)), SC / Sch-Fe / SRB materials ( Figure 3 ) can clearly be seen from the SEM that the spherical Schreiberite and the lamellar sludge charcoal are combined together, and rod-shaped microorganisms are loaded on its surface, indicating that the microorganisms in the newly prepared material are successfully immobilized on the sludge charcoal-loaded Schreiberite material.

[0067] Potassium antimony tartrate was dissolved in sterile distilled water to prepare a Sb(V) solution with a concentration of 50 mg / L; 0.1 g of Sch (Schner mineral), Sch-Fe / SRB (Schner mineral loaded with iron-sulfur-reducing bacteria), SC (sludge charcoal), SC-Fe / SRB (sludge charcoal loaded with iron-sulfur-reducing bacteria), SC / Sch (sludge charcoal loaded with Schner mineral material in Example 1), N-SC / Sch-Fe / SRB (sludge charcoal loaded with Schner mineral-immobilized iron-sulfur-reducing bacteria in Comparative Example 3) and SC / Sch-Fe / SRB material in Example 1 were weighed in conical flasks, mixed, and placed in a constant temperature shaking box for 48 h, and the supernatant was taken and the concentration of Sb in the solution was determined by atomic absorption spectrophotometer.

[0068] After 2 days of reaction, the adsorption amounts of Sb by Sch, Sch-Fe / SRB, SC, SC-Fe / SRB, SC / Sch, N-SC / Sch-Fe / SRB and SC / Sch-Fe / SRB were measured to be 17.35, 45.23, 20.22, 35.67, 18.32, 41.77 and 75.09 mg / g, respectively (Table 1). It can be seen that compared with Schmidt mineral, Schmidt mineral loaded with iron-sulfur-reducing bacteria, sludge charcoal, sludge charcoal loaded with iron-sulfur-reducing bacteria, sludge charcoal loaded with Schmidt mineral and the ordinary sludge charcoal loaded with Schmidt mineral immobilized with iron-sulfur-reducing bacteria prepared in Comparative Example 3, the composite material (SC / Sch-Fe / SRB) obtained by the present invention by combining the Schmidt mineral matrix material synthesized in the sludge charcoal loading process with iron-sulfur-reducing bacteria has a significant improvement in the removal rate of Sb, indicating that the three materials have a significant synergistic effect, so that the entire composite material shows a good Sb removal effect.

[0069] Example 2

[0070] A preparation method of a sludge charcoal-loaded Schroeder mineral-immobilized iron-sulfur-reducing bacteria composite material (SC / Sch-Fe / SRB), the specific steps are as follows:

[0071] The selected strains are the same as in Example 1.

[0072] Preparation of sludge charcoal: Place the printing and dyeing sludge in an oven, adjust the temperature to 45°C, and dry it to a sludge moisture content of 8%. Place the dried sludge in a tubular furnace for anaerobic pyrolysis at a pyrolysis temperature of 550°C and a pyrolysis time of 2.5h. During the pyrolysis, the nitrogen flow rate is controlled at 40mL / min. Grind the pyrolyzed sample through a 200-mesh sieve to obtain sludge charcoal.

[0073] Preparation of sludge-loaded Schrödinger mineral material (SC / Sch): 22.42 g of ferrous sulfate heptahydrate (FeSO4·7H2O) was dissolved in 1 L of deionized water, and 5.6 g of the above-mentioned sludge was added. After stirring evenly, 12 mL of 30% hydrogen peroxide (H2O2) solution was slowly added using a peristaltic pump. The mixture was fully reacted for 36 h at room temperature, and centrifuged at 7000 rpm for 4 min. The solid in the mixture was collected and washed with a dilute acid solution with a pH of 2 and deionized water until the pH value of the washing solution remained constant. Finally, the washed solid was freeze-dried at -65 ° C for 36 h, and then ground through a 200-mesh sieve to obtain a sludge-loaded Schrödinger mineral sample.

[0074] Preparation of SC / Sch-Fe / SRB material: The above-screened microorganism Cedecea sp. ISRB13 (2 mL of strain stock solution) was activated in LB medium (100 mL) for 36 h, and then the above-mentioned sludge-loaded Schrödinger mineral material was added, mixed and shaken, and sterile liquid paraffin was gently added to seal the liquid surface. The thickness of the sterile liquid paraffin was 2.5 cm. The stopper was plugged tightly and cultured at a constant temperature of 25 °C for 36 h until the entire culture medium showed a thick black color (the bacterial concentration at this time was 10×10 9 CFU / mL), obtain a modified product solution, then centrifuge at 7000 rpm for 4 minutes and wash with physiological saline, repeat the operation 4 times, freeze-dry the washed solid at -60°C for 36 hours, grind the obtained solid through a 200-mesh sieve to obtain the SC / Sch-Fe / SRB material.

[0075] Potassium antimony tartrate was dissolved in sterile distilled water to prepare a 50 mg / L Sb(V) solution. 0.1 g SC / Sch-Fe / SRB material was weighed into a conical flask, mixed and placed in a constant temperature shaker for 48 h. The supernatant was taken and the concentration of Sb in the solution was determined by an atomic absorption spectrophotometer.

[0076] After 2 days of reaction, the adsorption amount of Sb by SC / Sch-Fe / SRB prepared in Example 2 was 64.64 mg / g (Table 1), indicating that the SC / Sch-Fe / SRB of the present invention has a high removal rate and good removal effect for Sb.

[0077]

[0078] Example 3

[0079] The SC and SC / Sch-Fe / SRB materials obtained in Example 1 were used to remove heavy metal Cd(II).

[0080] Potassium antimony tartrate was dissolved in sterile distilled water to prepare a Cd(II) solution with a concentration of 50 mg / L; 0.1 g of SC and SC / Sch-Fe / SRB materials were weighed and placed in a conical flask, mixed and placed in a constant temperature shaking box for 48 h, and then the supernatant was taken and the concentration of Cd(II) in the solution was determined by an atomic absorption spectrophotometer.

[0081] It was measured that the adsorption amounts of Cd(II) by SC and SC / Sch-Fe / SRB in Example 1 after 2 days of reaction were 13.22 mg / g and 40.19 mg / g, respectively, indicating that the SC / Sch-Fe / SRB composite material prepared by the present invention can greatly improve the removal rate of Cd(II) and exhibit an excellent Cd(II) removal effect.

[0082] Example 4

[0083] The SC and SC / Sch-Fe / SRB materials obtained in Example 1 were used to remove heavy metal Pb(II).

[0084] Lead nitrate was dissolved in sterile distilled water to prepare a Pb(II) solution with a concentration of 200 mg / L; 0.1 g of SC and the SC / Sch-Fe / SRB material prepared in the example were weighed into a conical flask, respectively, and the mixture was placed in a constant temperature shaking box for 48 h, and the supernatant was taken and the Pb(II) concentration in the solution was determined by an atomic absorption spectrophotometer.

[0085] It was measured that after 2 days of reaction, the adsorption capacity of Pb(II) by SC was 23.56 mg / g, while the adsorption capacity of Pb(II) by SC / Sch-Fe / SRB material in Example 1 reached 156.33 mg / g. It can be seen that the removal rate of Pb(II) by the sludge charcoal-loaded Sch-Fe mineral-immobilized iron-sulfur-reducing bacteria composite material of the present invention is significantly improved, showing excellent adsorption and removal effect.

Claims

1. A method for preparing a composite material of sewage sludge charcoal loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria, characterized in that: The sludge is subjected to high-temperature pyrolysis to obtain sludge charcoal; the sludge charcoal is mixed with a ferrous sulfate solution and then a hydrogen peroxide solution is added to perform an oxidation reaction, and the sludge charcoal-loaded Schrödinger mineral material is obtained by solid-liquid separation; the sludge charcoal-loaded Schrödinger mineral material is added to a culture medium containing iron-sulfur-reducing bacteria and the bacteria are cultured until the culture medium turns black, and then the solid-liquid separation is performed to obtain the sludge charcoal-loaded Schrödinger mineral material.

2. The method for preparing a composite material of sewage sludge charcoal loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria according to claim 1, characterized in that: The conditions for high temperature pyrolysis are: the atmosphere is a protective atmosphere, the temperature is 400-600° C., and the time is 2-3 hours.

3. The method for preparing a composite material of sewage sludge charcoal loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria according to claim 1 or 2, characterized in that: The mass ratio of the sludge charcoal to the iron element in ferrous sulfate is 0.5-2:

1.

4. The method for preparing a composite material of sewage sludge charcoal loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria according to claim 1, characterized in that: The molar concentration of the ferrous sulfate solution is 0.06-0.1 mol / L.

5. The method for preparing a composite material of sewage sludge charcoal loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria according to claim 1 or 4, characterized in that: The concentration of hydrogen peroxide in the reaction system is 11.12-16.67 g / L.

6. The method for preparing a composite material of sewage sludge charcoal loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria according to claim 1, characterized in that: The iron-sulfur reducing bacteria is Cedecea sp. ISRB13.

7. The method for preparing a composite material of sewage sludge charcoal loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria according to claim 1, characterized in that: The bacterial culture conditions are: temperature of 25-35°C and time of 24-48h.

8. The method for preparing a composite material of sewage sludge charcoal loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria according to claim 1, 6 or 7, characterized in that: The concentration of the bacterial strain after bacterial culture is 5~10×10 9 CFU / mL.

9. A composite material of sewage sludge charcoal loaded with Schweiner mineral and immobilized iron-sulfur-reducing bacteria, characterized in that: Prepared by the method described in any one of claims 1 to 8.

10. The use of the composite material of sewage sludge charcoal loaded with Schweiner mineral-immobilized iron-sulfur-reducing bacteria according to claim 9, characterized in that: Used to adsorb and remove heavy metal ions in liquids.

Citation Information

Patent Citations

  • Method for repairing heavy metal-contaminated soil by combining sludge biochar immobilized bacteria with plants

    CN112387778A

  • Method for repairing chromium-contaminated soil through biochar-loaded hematite-shewanella loihica complex

    CN113058983A

  • Method for preparing biomass charcoal by using bamboo papermaking sludge

    CN113262755A

  • Biochar microbial active soil conditioner and preparation method thereof

    CN116656378A

  • Schwertmannite iron-based biochar composite material as well as preparation and application thereof

    CN117105432A

Cited By

  • Preparation method and application of hydrothermal carbon loaded SRB composite material

    CN122212374A

  • Method for enhancing biological leaching of arsenopyrite and synchronously fixing arsenic by using biological source Schwertmannite

    CN122445920A